The Relationship between LDL/ HDL Ratio and Coronary Lesion Severity Measured by Syntax Score in Patients with Non-Elevation Acute Myocardial Infarction at Hajj Adam Malik General Hospital, Medan - Hashmi, T. Rifqi; Hasan, Harris; Lubis, Hilfan Ade Putra (CoinReads Media Prima, 2024)
Introduction: Coronary artery disease (CAD), results from reduced myocardial perfusion leading to angina, myocardial infarction (MI), and/or heart failure. It accounts for one third to one half of cardiovascular cases. A higher SYNTAX score indicates a more complex condition and poorer prognosis in patients undergoing coronary revascularization especially with PCI. This study aims to determine how the LDL/HDL ratio relates to the complexity of coronary lesions (Syntax Score) in coronary heart disease based on characteristics. Methods: The type of this study was observational analytic retrospective with a cross sectional design. The study was conducted using secondary data through medical record data of patients diagnosed with NSTEMI. Results: The subjects were 60 people with an average age of 58,1±8,629. It was found that the mean value of the LDL/HDL ratio was 3,95±3,837, in patients with an LDL/HDL ratio ≥ 2.517 it was found that there were 40 sample(66.7%) of whom had a lesion severity level of Syntax score ≥23 ,27 samples (45%), and in patients with an LDL/HDL ratio < 2.517, 20 samples (33.3%) were found to have a lesion severity level of Syntax score ≥ 23 with 4 samples (6.7%). Conclusion: There is a relationship between the LDL/HDL ratio and the severity of CAD based on the Syntax score with LDL/HDL ratio values being higher in patients with moderate-severe CAD than in patients with mild CAD.